ANALISIS KINERJA KEUANGAN PEMERINTAH KOTA JAMBI TAHUN 2015-2024 - Valencia Olivia Tambunan; Zulfanetti; Deki Irawan (STKIP Subang, 2026)
This study aims to analyze the financial performance of the Jambi City Government during the 2015–2024 period by using several financial ratios, namely the Fiscal Decentralization Degree Ratio, Regional Financial Independence Ratio, Local Own-Source Revenue (PAD) Effectiveness Ratio, Regional Financial Efficiency Ratio, and Harmony Ratio. The research employed a quantitative descriptive method using secondary data obtained from the Budget Realization Reports (Laporan Realisasi Anggaran/LRA) of the Jambi City Government from 2015 to 2024. The analysis was conducted by calculating and interpreting each financial ratio to assess the regional government’s financial capability, independence, efficiency, and effectiveness in managing regional finances. The results indicate that the financial performance of the Jambi City Government based on the Fiscal Decentralization Degree Ratio was categorized as moderate, reflecting that regional revenue still depended significantly on transfers from the central government. The Regional Financial Independence Ratio was categorized as low with a consultative relationship pattern, indicating limited fiscal independence. Furthermore, the PAD Effectiveness Ratio showed a fairly effective performance, while the Regional Financial Efficiency Ratio was considered inefficient. Meanwhile, the Harmony Ratio indicated that the allocation between operational expenditure and capital expenditure was relatively balanced. Overall, the financial performance of the Jambi City Government during the study period was categorized as fairly good, although improvements in regional revenue optimization and expenditure efficiency are still required.